Respon Pertumbuhan dan Hasil Tanaman Selada Merah (Lactuca sativa L.) Varietas Red Rapid Akibat Pemberian Air Fermentasi Limbah Organik - Copertino, Yosef Arby; Sugiono, Darso; Rahmi, Hayatul (JURNAL AGROPLASMA, 2025)
The less optimal management of organic waste results in waste still accumulating without any follow-up actions. Efforts to reduce the spike in organic waste piles can be made by utilizing it as fermentation water. This study aims to determine the effect of providing fermentation water from organic waste on the yield and growth of red lettuce, variety Red Rapid. The research method uses an experimental method with a Single Factor Completely Randomized Block Design (RBD). The factor tested is the addition of fermentation water from organic waste, which consists of 5 treatments and is repeated 5 times. The treatments used include A (Control 0 ml/l), B (Concentration 100 ml/l), C (Concentration 200 ml/l), D (Concentration 300 ml/l), and E (POC NASA 5 ml/l). The effect of the treatments was analyzed using variance analysis, and if tested with F at a 5% significance level, it would proceed with the DMRT (Duncan Multiple Range Test) at a 5% level. The results of the study show that treatment C The concentration of Fermented Water from organic waste at 200 ml/l yielded the highest results for the number of leaves at 28 days after planting (23.6 leaves),  Keywords: fermented water, organic waste, red lettuce (Lactuca sativa L.)